Propuesta de guía para la gestión del establecimiento de un Parque Temático Científico-Turístico en el CATIE - Torres-Camacho, Leonardo (Instituto Tecnológico de Costa Rica, 2016)
The Tropical Agricultural Research and Higher Education Center (CATIE), is an international university at the graduate level that educates and trains leaders in agriculture, natural resources and related fields to meet the challenges and opportunities of a changing world. For this, CATIE has graduate teaching programs renowned for their quality and track record; they teach what he does with hundreds of partners in many countries, and share the progress and status of science and technology in different fields of interest, demands and needs of today's world This research proposes a management plan based on project management, and specifically for the establishment of the Scientific-Tourist Theme Park (CATIE). To develop the proposed project management plan is necessary to identify lessons learned and best practices developed by companies that provide tourism services relating to conservation and to determine the assets of the processes of the organization. Likewise the technical and cultural organization that may affect the proposed factors are determined. Once completed the analysis of the current maturity level for project management in the institution, it will show that does not have a standard methodology for managing projects, and also lacks metrics, policies, procedures and specific tools to assess the performance of projects, and can be applied in the management of the theme park. The development of the proposed methodology is based on the PMBOK (Guide to the Project Management for PMI®) and since CATIE, is an organization whose main source of income are the projects the proposed methodology can be applied to other areas of the organization. xviii Finally it is concluded that due to the lack of a specific methodology for project management, it is necessary to establish a standard in activities and tools to make project management to be successful.
Proyecto de Graduación (Maestría en Gerencia de Proyectos) Instituto Tecnológico de Costa Rica, Escuela de Ingeniería en Computación, Administración de Empresas, Ingeniería en Construcción, 2016.
Keywords: Turismo; Clientes; SINAC; Análisis FODA; Germoplasma